PENINGKATAN KUALITAS PENGAJAR BAHASA ARAB SEBAGAI UPAYA MENINGKATKAN STANDAR MUTU PEMBELAJARAN BAHASA ARAB - Abdul Wahab Rosyidi (SCAD Independent, 2014)
In reality, the objectives, methods, 'and materials of teaching and learning Arabic have not improved the Arabic students' achievements. One of the causes is the unqualified teachers', they do not have enough knowledge of applied linguistic theories, the principles, approches, and methods of language learning, and material improvement. While, teachers' have important roles in Arabic learning process. The success of Arabic learning results from, among other things, the teachers' abilities that inclued